Non-infectious uveitis: A review of clinical, diagnostic and therapeutic approach to the disease (Research, Society and Development, 2024)
The incidence of non-infectious uveitis (NIU) is influenced by genetic and environmental factors. This disease has a clinical picture similar to other eye pathologies, it becomes difficult to obtain accurate diagnosis. The research aims to review the clinical, diagnostic and therapeutic approach of NIU. To achieve this objective, there was a bibliographic review study based on therapeutic guidelines and scientific articles published in MedLINE from 2018 to 2023. The evidence presented based on the investigated literature gives us that before starting to the Therapy, it is necessary to perform the proper diagnosis and choose the best therapy that preserves anatomical structures and improves the patient's vision. In addition, it is worth mentioning that the base of NIU treatment remains immunosuppressants and corticosteroids, the latter known for having eye and systemic side effects. Currently to minimize these effects, therapy has been introduced with biological products, which provides better visual acuity, reduces intraocular inflammation, decreases the systemic dose of corticosteroids and minimizes adverse effects. However, its use requires caution as it has already been reported to occur demyelinating disorders in a small group of patients. NIU is always associated with a systemic or idiopathic autoimmune condition. Thus, for a good clinical, diagnostic and therapeutic approach, it is necessary that there is close collaboration between the ophthalmologist and doctors of other specialties (rheumatologist) to have an accurate diagnosis and discard other associated comorbidities, avoiding complications that cause blindness.